2018
DOI: 10.1016/j.orggeochem.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oxygen exposure on long-chain alkyl diols and the long chain diol index (LDI) – a long-term incubation study

Abstract: a b s t r a c tIn recent years, long chain alkyl diols (LCDs) have been used increasingly to study and reconstruct past sea surface temperatures using the long chain diol index (LDI), which is based on changes in the distribution of 1,15-LCDs. However, the impact of diagenesis on LCDs and the LDI is still poorly constrained. Here we studied the impact of oxygen exposure on LCDs and the LDI, by aerobically incubating biomass of the LCD-producing alga Nannochloropsis oculata for 271 days. The concentrations of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…This suggests that degradation in the water column does not affect the LDI proxy. This is in agreement with Reiche et al (2018) who performed a short-term degradation experiment (< 1 year) and found that the LDI index was not affected by oxic exposure on short timescales. However, the oxygen exposure time on the seafloor is much longer; Rodrigo-Gámiz et al (2016) showed for sediments in the Arabian Sea (deposited under a range of bottom water oxygen conditions) that different LCDs had different degradation rates, which compromised the LDI ratio.…”
Section: Preservation Of Lcdssupporting
confidence: 92%
“…This suggests that degradation in the water column does not affect the LDI proxy. This is in agreement with Reiche et al (2018) who performed a short-term degradation experiment (< 1 year) and found that the LDI index was not affected by oxic exposure on short timescales. However, the oxygen exposure time on the seafloor is much longer; Rodrigo-Gámiz et al (2016) showed for sediments in the Arabian Sea (deposited under a range of bottom water oxygen conditions) that different LCDs had different degradation rates, which compromised the LDI ratio.…”
Section: Preservation Of Lcdssupporting
confidence: 92%
“…Since lipid extraction techniques mostly used to analyze fatty acid derivatives usually cleave ester linkages but are ineffective toward ether-bound lipids, the cellular abundance of eustigmatophycean LCDs, that are thought to be mostly ether-bound, are likely to be significantly higher than those typically measured. The incubation of N. oculata biomass in the dark, under aerobic conditions, resulted in a sharp increase of LCDs after 100 days, confirming that LCDs can derive from algaenan degradation (Reiche et al, 2018). The chemical structure of algaenans still requires to be fully elucidated, but their high stability against chemical and biological degradation makes these compounds promising for the development of sustainable materials.…”
Section: Long Chain Diols and Long Chain Alkenols As Cell Wall Building Blocksmentioning
confidence: 93%
“…For example, the LCD content in Nannochloropsis spp. can be up to two orders of magnitude lower than that of EPA (Reiche et al, 2018) or monounsaturated and saturated fatty acids (Balzano et al, 2017). The production of substantial amounts of fatty acid derivatives in microalgae is thus more time consuming and risks being economically unviable.…”
Section: State Of Art Of Microalgal Fatty Acid Derivativesmentioning
confidence: 99%
“…The Cariaco Basin is one of the largest marine anoxic basins (Richards, 1975), located on the continental shelf of Venezuela. The basin is characterized by permanent stratification and is strongly influenced by the migration of the intertropical convergence zone (ITCZ).…”
Section: Cariaco Basinmentioning
confidence: 99%